2019
DOI: 10.4081/ripppo.2019.388
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of Jeremy Safran

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As widely documented in the literature, personality disordered patients present major difficulties in constructing and maintaining the therapeutic alliance. Such patients represent a great challenge for clinicians, as evidenced by Safran and Muran’s studies (Muran, Safran, Samstag, & Winston, 2005 ; Muran et al, 2009 ; Muran, Segal, Samstag, & Crawford, 1994 ) and confirmed by further research (Bender, 2005 ; Colli, Gentile, Condino, & Lingiardi, 2019 ; Smith, Hilsenroth, Fiori, & Bornstein, 2014 ; Tanzilli, Colli, Gualco, & Lingiardi, 2018 ). In their qualitative study Dropout and narcissism: an exploratory research about situational factors and personality variables of the psychotherapist (2019, pp.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…As widely documented in the literature, personality disordered patients present major difficulties in constructing and maintaining the therapeutic alliance. Such patients represent a great challenge for clinicians, as evidenced by Safran and Muran’s studies (Muran, Safran, Samstag, & Winston, 2005 ; Muran et al, 2009 ; Muran, Segal, Samstag, & Crawford, 1994 ) and confirmed by further research (Bender, 2005 ; Colli, Gentile, Condino, & Lingiardi, 2019 ; Smith, Hilsenroth, Fiori, & Bornstein, 2014 ; Tanzilli, Colli, Gualco, & Lingiardi, 2018 ). In their qualitative study Dropout and narcissism: an exploratory research about situational factors and personality variables of the psychotherapist (2019, pp.…”
mentioning
confidence: 87%
“…This is Part II of a special issue, Research in Psychotherapy: Psychopathology, Process and Outcome , dedicated in memory of our colleague Jeremy Safran (Part I was published in April 2019). For a recollection of the human and professional figure of Jeremy and a contextualization of this special issue in the theoretical, clinical, and research framework on the therapeutic alliance, please refer to our introductory notes in Part I (Lingiardi & Gentile, 2019 ).…”
mentioning
confidence: 99%